Enshrining European Directives in training regulations : the example of the inland shipping occupations - Bretschneider, Markus [Verfasser]; Telieps, Johanna [Verfasser] (My University, 2022)
"Ordinances relating to the training occupations of inland bargeman/woman specialising in freight shipping, inland bargeman/woman specialising in passenger shipping and inland shipping captain will enter into force on 1 August 2022. New EU guidelines needed to be taken into account during some parts of the process of drawing up the training contents and examination requirements. This article describes the challenges that had to be overcome whilst developing these two training regulations and also outlines the solutions that were found in order to harmonise domestic and European standards." (BIBB-Doku)
Keywords: S 2.2.1 Ordnung von Ausbildungsberufen; S 6.4.2.1 Verkehrsberufe (inkl. Nachrichtenverkehr); 370; Neuordnung der Ausbildungsberufe; Binnenschiffer; Rechtliche Regelungen; EU-Recht